Analysis of the Effectiveness of the STAD Type Cooperative Learning Model in Improving Volleyball Learning Outcomes of Elementary School Students - Purnawan, Purnawan; Lian, Bukman; Kristina, Putri Cicilia (Yayasan Sembilan Pemuda Indonesia, 2023)
This study was conducted with the aim of determining the effectiveness of the STAD type cooperative learning model in improving volleyball learning outcomes of elementary school students. This research uses the research method of literature study. This type of research data collection is a literature review whose purpose is to find out how the STAD type cooperative learning model in improving volleyball learning outcomes of elementary school students. Data collection techniques are obtained from several relevant sources related to the research being researched. The relevant sources that have been collected are then compiled, analyzed, and concluded so as to conclude that the application of the STAD type cooperative learning model in learning activities can help students improve volleyball learning outcomes in elementary school students.